SINTESIS KOMPOSIT SELULOSA/KITOSAN–Fe₃O₄ sEBAGAI KANDIDAT KATALIS HETEROGEN REAKSI FENTON - Utami Irawati; Nafia Fitrawati; Sunardi (University of Bengkulu, 2026)
This study aims to develop and evaluate the performance of cellulose/chitosan–Fe₃O₄ composites as heterogeneous catalysts in the Fenton reaction system for methylene blue degradation. Cellulose was isolated from sawdust and combined with chitosan, alginate, and magnetite particles to form various composite variations. The composites were characterized using FTIR, SEM, and XRD. The results showed that the addition of magnetite increased the Fe content in the composites, strengthened intermolecular interactions, and produced crystalline magnetite phases as detected by XRD. These findings support the potential application of a biopolymer-based cellulose–chitosan composites to be used as environmentally friendly catalysts for dye degradation for textile wastewater treatment. Keywords: magnetite composite; heterogenous catalyst; Fenton reaction; dye degradation